2018
DOI: 10.18520/cs/v114/i06/1275-1283
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Costing of Road Traffic Accidents:Evidence from Nagpur City, Maharashtra, India

Abstract: Road traffic accidents (RTAs) have become a serious problem worldwide as they incur losses of around 2% of a country's gross domestic product (GDP). RTAs are one of the major causes of death and injury in developing countries like India. To enable governments to take policy decisions on road safety, it is necessary that good research is undertaken to estimate the cost of accidents. This kind of study will help governments make important decisions on investment in traffic safety, improvement of roads and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Studies have shown that up to two-thirds of injuries and deaths from RTCs in India are reported in those between the ages of 15 and 40 years [9,31,51,52]. This group includes the most economically active population, most of whom are males [36,52,53]. These ndings are in keeping with the results from our study where participants described the economic impact of RTCs on families and the country as a whole through the loss of this economically productive group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies have shown that up to two-thirds of injuries and deaths from RTCs in India are reported in those between the ages of 15 and 40 years [9,31,51,52]. This group includes the most economically active population, most of whom are males [36,52,53]. These ndings are in keeping with the results from our study where participants described the economic impact of RTCs on families and the country as a whole through the loss of this economically productive group.…”
Section: Discussionsupporting
confidence: 90%
“…A case study carried out in Bangalore, another city in India, showed that affected households tended to resort to borrowing money or selling assets to cope not only with the loss of income but with the cost of caring for the injured family member [54]. Less than 20 percent received any compensation from the government, employees or insurance companies [53]. This is a common scenario in India, where many families end up spending more than 10 times their monthly income for the immediate and longterm management of the RTC victim [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accidents occasionally cause psychological imbalance (mental imbalance) or tension, which cannot be envisioned. Higher clinical charges or medical costs for major injuries have additionally been said in earlier studies [12]- [13]. The losses related to human capital cost have been comparatively lower than minor injuries, at around 7.7% and 21.5% for most major accidents, as victims could commonly go back to normal condition after restoration.…”
Section: Resultsmentioning
confidence: 89%
“…Studies have shown that up to two-thirds of injuries and deaths from RTCs in India are reported in those between the ages of 15 and 40 years [ 10 , 34 , 68 , 69 ]. This group includes the most economically active population, most of whom are males [ 39 , 69 , 70 ]. These findings are in keeping with the results from our study where participants described the economic impact of RTCs on families and the country as a whole through the loss of this economically productive group.…”
Section: Discussionmentioning
confidence: 99%
“…A case study carried out in Bangalore, another city in India, showed that affected households tended to resort to borrowing money or selling assets to cope not only with the loss of income but with the cost of caring for the injured family member [ 71 ]. Less than 20% received any compensation from the government, employees or insurance companies [ 70 ]. This is a common scenario in India, where many families end up spending more than 10 times their monthly income for the immediate and long-term management of the RTC casualty [ 72 ].…”
Section: Discussionmentioning
confidence: 99%